2022
DOI: 10.1002/anie.202213026
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Assisted Metal–Air Batteries: Progress, Challenges, and Perspectives

Abstract: Metal-air batteries are considered one of the most promising next-generation energy storage devices owing to their ultrahigh theoretical specific energy. However, sluggish cathode kinetics (O 2 and CO 2 reduction/evolution) result in large overpotentials and low round-trip efficiencies which seriously hinder their practical applications. Utilizing light to drive slow cathode processes has increasingly becoming a promising solution to this issue. Considering the rapid development and emerging issues of this fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 176 publications
(220 reference statements)
0
26
0
Order By: Relevance
“…[43] Furthermore, illumination also could influence product growth routes. [44] Xu et al reported that, without illumination, large-sized Li 2 O 2 products generated randomly covered on the TiO 2 -Fe 2 O 3 photocathode via a solution-mediated growth pathway. [45] than the disproportionation reaction (red).…”
Section: Surface Growthmentioning
confidence: 99%
“…[43] Furthermore, illumination also could influence product growth routes. [44] Xu et al reported that, without illumination, large-sized Li 2 O 2 products generated randomly covered on the TiO 2 -Fe 2 O 3 photocathode via a solution-mediated growth pathway. [45] than the disproportionation reaction (red).…”
Section: Surface Growthmentioning
confidence: 99%
“…In this regard, desired photocatalysts should be empowered with sufficient photocatalytically active areas and an appropriate band structure to meet the requirements of broad light absorption. [ 139 ] On top of that, the selective adsorption of the specific solar spectrum to flexibly regulate the electronic structure of heterophotocatalysts sounds promising as well. [ 143 ]…”
Section: Comparison Of Various Field‐assisted Electrocatalysismentioning
confidence: 99%
“…The photo-assisted ZIB broadens the operating conditions and environment of zinc-ion batteries [ 20 ]. In 2022, photo-assisted zinc-CO 2 batteries were proposed to mitigate the greenhouse effect [ 21 ].…”
Section: Introductionmentioning
confidence: 99%